Investigation of the possibility of balancing aerodynamic imbalance of the impeller of the axial fan by correction of masses - Филимонихин, Геннадий Борисович; Олийниченко, Любовь Сергеевна (Eastern-European Journal of Enterprise Technologies, 2015)
Investigate the possibility of balancing of ordinary and aerodynamic imbalances of the impeller of the axial fan by correction of mass. It is assumed that the impeller is made inaccurate. Using the Zagordan’s theory of impeller were found the resultant vector and the resultant moment of the aerodynamic forces acting on rotating in the initial still air (gas) axial fan impeller. Find the corresponding their aerodynamic imbalance. It established its analogy with the imbalance of the unbalanced mass. Also, found its difference consisting in dependence of the aerodynamic imbalance on the density of air (gas). Was concluded about the possibility of balancing aerodynamic and ordinary imbalances by correction of mass before operating the fan. Was concluded about the possibility of static or dynamic balancing by passive auto-balancers of ordinary and aerodynamic imbalances during fan operation.